The Overview of The Methods of Textual Analysis - Zulfiya, Tukhtakhodjaeva (Innovative Technologica: Methodical Research Journal, 2024)
Textual analysis, an integral part of linguistics, encompasses a variety of methods for studying text structures, meanings, and functions. This article provides a comprehensive overview of the methodologies employed in textual analysis, including componential analysis, pragmatic analysis, cognitive metaphorical analysis, and corpus linguistic analysis. It also examines the interdisciplinary applications of these methods in language teaching, cultural studies, and computational linguistics. By integrating theoretical and practical perspectives, the article highlights the contributions of textual analysis to understanding the multifaceted nature of texts and fostering linguistic competence.